2017
DOI: 10.3126/njh.v14i2.18496
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic right heart study in patients with chronic obstructive pulmonary disease

Abstract: Background and Aims: : Chronic obstructive pulmonary disease (COPD) is highly prevalent in the Nepalese population. It is associated with significant extrapulmonary effects among which cardiovascular complications are most common . Echocardiography evaluation mainly focused on effects on the right heart function is a salient tool to evaluate the presence of degree of pulmonary hypertension and also identify those group of patients who need more early aggressive therapy for the underling lung disease . We aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
1
Order By: Relevance
“…In one of them, the 5-year survival rates were 50% in patients with mild PH (20-30 mmHg), 30% in those with moderate to severe PH (30-50 mmHg), and 0% in the small group of patients with severe PH (> 50 mmHg) [30]. As a conclusion, the high level of PH is associated with poor prognosis in COPD patients [7].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In one of them, the 5-year survival rates were 50% in patients with mild PH (20-30 mmHg), 30% in those with moderate to severe PH (30-50 mmHg), and 0% in the small group of patients with severe PH (> 50 mmHg) [30]. As a conclusion, the high level of PH is associated with poor prognosis in COPD patients [7].…”
Section: Discussionmentioning
confidence: 87%
“…The difference can be explained by several factors like the type of equipment used, the experience of the operator, the quality of the image obtained or the body habitus. Impairment of RV function and alteration of pulmonary blood vessels complicate the clinical course of COPD and correlates inversely with the survival of these patients [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RV fonksiyonunda bozulma ve pulmoner kan damarlarında değişiklik olması KOAH' ın klinik seyrini zorlaştırır ve bu hastaların sağ kalımı ile ters orantılıdır 28 . KOAH hastalarında RV' nin hem sistolik hem de diyastolik fonksiyonlarının bozulduğu iyi bilinmektedir.…”
Section: Discussionunclassified
“…Most of the studies were either of low (n ¼ 13) or moderate (n ¼ 12) quality, with two classed as high quality. Some studies reported on more than one condition, with the major diseases identified being: COPD (22 studies), 31,32,[34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] asthma (8 studies), 20,32,36,37,49,[52][53][54] bronchiectasis (2 studies and as a co-morbidity in one), 30,40,52 restrictive lung diseases (3 studies), 49,51,52 and 'chronic bronchitis' (1 study). 29 Symptoms reported included chronic cough, phlegm or sputum production, breathlessness or shortness of breath, chest tightness, wheezing, dyspnoea and sore throat.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%